Comparative analysis reveals the modular functional structure of conjugative megaplasmid pTTS12 of Pseudomonas putida S12: A paradigm for transferable traits, plasmid stability, and inheritance? - Kusumawardhani, Hadiastri; Hosseini, Rohola; Verschoor, Jo-Anne; de Winde, Johannes H. (Frontiers in Microbiology, 2022)
Originating from various environmental niches, large numbers of bacterial plasmids have been found carrying heavy metal and antibiotic resistance genes, degradation pathways and specific transporter genes for organic solvents or aromatic compounds. Such genes may constitute promising candidates for novel synthetic biology applications. Our systematic analysis of gene clusters encoded on megaplasmid pTTS12 from Pseudomonas putida S12 underscores that a large portion of its genes is involved in stress response to increase survival under harsh conditions like the presence of heavy metal and organic solvent. We investigated putative roles of genes encoded on pTTS12 and further elaborated on their roles in the establishment and maintenance under several stress conditions, specifically focusing on solvent tolerance in P. putida strains. The backbone of pTTS12 was found to be closely related to that of the carbapenem-resistance plasmid pOZ176, member of the IncP-2 incompatibility group, although the carbapenem resistance cassette is absent from pTTS12. Megaplasmid pTTS12 contains multiple transposon-flanked cassettes mediating resistance to various heavy metals such as tellurite, chromate (Tn7), and mercury (Tn5053 and Tn5563). Additionally, pTTS12 also contains a P-type, Type IV secretion system (T4SS) supporting self-transfer to other P. putida strains. This study increases our understanding in the modular structure of pTTS12 as a member of IncP-2 plasmid family and several promising exchangeable gene clusters to construct robust microbial hosts for biotechnology applications.